الإكتفاء في مغازي المصطفي صلى الله عليه وسلم - Al-Kalami | الكلامي, Suleiman bin Musa | سليمان بن موسي (King Saud University | جامعة الملك سعود, 2023)
A good copy, written by a good Moroccan. The first part of it was printed as it was mentioned in the media, and there is a part that begins with the conquest of Egypt and ends at the end of the book. There is almost a copy held in the University of Riyadh - Central Library | نسخة حسنة ، خطها مغربي حسن ، طبع الجزء الأول منه كما ورد فى الاعلام و الموجود جزء يبدأ بفتح مصر و ينتهي بنهاية الكتاب. هناك نسخة مقتناة تقريبا فى جامعة الرياض - المكتبة المركزية